RANCANG BANGUN SISTEM INFORMASI PEMBAYARAN SUMBANGAN PEMBINAAN PENDIDIKAN (SPP) BERBASIS WEB MENGGUNAKAN WHATSAPP GATEWAY PADA SMK BINA INSAN MANDIRI - Ramdhani, Muhamad Januar (Sekolah Tinggi Ilmu Komputer El Rahma, 2025)
This study aims to design and develop a web-based information system for educational payment (SPP) integrated with a WhatsApp Gateway at SMK Bina Insan Mandir. The system is developed to overcome various challenges in managing student payment transactions that are currently handled manually and inefficiently. The research employs the Research and Development (R&D) methodology using the Waterfall model, which includes stages of requirement analysis, system design, implementation, and testing. The system is built using PHP 8.3 and the Laravel framework, with MySQL as the database. The application can manage student data, record payment transactions, generate financial reports, and automatically send payment notifications to parents via WhatsApp Gateway. The testing results, conducted through Black Box Testing and User Acceptance Testing (UAT), show that the system functions according to user needs with an accuracy rate of 89%, categorized as